Kajian Kerjasama antar Pemangku Kepentingan dalam Program Pengembangan Klaster Tanaman Obat (Biofarmaka) di Kecamatan Tengaran Kabupaten Semarang Tahun 2011-2013 - hani, dea aprilaga; Widayati, Wiwik; Taufiq, Ahmad (Journal of Politic and Government Studies, 2015)
Behind the many benefits and market demand for medicinal plants, the fate of medicinal plant farmers are still not enough prosperous. Therefore, the government has taken an initiative for the welfare of the medicinal plant farmers by initiated a policy that tends to support them. One of the policy was made by the Bank Indonesia which is invites other stakeholders such as BPN Central Java, Central Java Dinasperindag, BRI branch Ungaran, Plantation Office of Semarang regency, and PT. Sido Muncul in a program named "Cluster Development Program of Medicinal PlantsÂ  in Semarang Regencyâ€. Because of so many stakeholders were involved, the question arises how they divide the tasks and work, therefore the formulation of problem taken are: "How is the cooperation among stakeholders in the Cluster Development Program of Medicinal Plants in Tengaran District and what inhibiting factors were faced?".Based on the issues discussed, this research used qualitative research methods with analytical descriptive research type. The aim of this research was to understand how the process of determining the duties and obligations of the involved stakeholders and also explains how the program run and what inhibiting factors faced by the stakeholders. The data obtained is used to formulate a recommendation as a suggestion for the involved stakeholders.It can be concluded that at the beginning, Bank Indonesia held a focus group discussion to determine the duties and obligations of stakeholders, and then the memorandum of understanding was made by Bank Indonesia and stakeholers. Bank Indonesia used value chain approach to run the cluster development program. This approach is systematically considering the whole stage of the production process, to distribution to the consumer. In this program stakeholders held socialization and providing aid in form of equipments that can be used by farmers for cultivation of medicinal plants as well as post-harvest processing.communication and commitmentÂ  determine the success of a partnership, so both should really be done by involved stakeholders.Keywords :Â  Cooperation, Stakeholder, Cluster Development, Medicinal Plants